La trattabilità del paziente con aspetti antisociali nell’area di intervento della doppia diagnosi - Di Stefano, Federica; Petrucci, Manuel; Zucchini, Roberto; Atzori, Emanuela (Il sogno della farfalla, 2014)
The authors, after an excursus into the main contemporary perspectives with regard to the concepts of antisocialness and psychopathy, concentrate their attention on the complex relationship between the use of substances and personality. Given the high number of admissions of patients with a pathological use of psychotropic substances, it is necessary to differentiate the patients who present antisocial aspects and are treatable in a hospital environment from those definable as “pure psychopathical”: as their violent acts are disconnected from any communicative value, they withdraw from any interpretative or therapeutic possibility. The authors, after having reviewed the current literature on the predictive factors of positive or negative therapeutic responses in psychiatric ward admissions, analyze the group and institutional dynamics which involve staff members in a hospital context. These dynamics, if not faced and resolved, may cause errors in the diagnostic assessment and negatively condition the outcome of the treatment. To illustrate the themes discussed, the authors report a single-case research including a process-outcome assessment.